Penguatan Pasar Opak Gambir melalui Digital Branding untuk Meningkatkan Brand Awareness dan Daya Saing - Widayani, Anna; Mujiono, M; Fiernaningsih, Nilawati (Dharma: Jurnal Pengabdian Masyarakat, 2024)
The opak gambir Home Industry supports the green economy concept by utilizing local materials and environmentally friendly production techniques. IRT Opak Gambir has attempted to reach a wider market through digital technology, but faces obstacles due to lack of competence in optimizing digital marketing. To overcome this, assistance will be provided in strengthening the opak gambir market through branding awareness with digital visual branding and website development. This assistance aims to improve partner skills in implementing digital branding, which includes creating attractive visual content and optimizing websites to reach a wider audience. With better branding awareness, IRT opak gambir is expected to increase brand awareness and competitiveness in the digital era. The results of this activity are expected to support sustainable business growth and increase market acceptance of opak gambir products, in line with the green economy concept being promoted.